Dampak Artificial Intelligence dalam Pembelajaran Sekolah Menengah Atas - Setiawi, Agustina Purnami; Patty, Elyakim Nova Supriyedi; Making, Samuel Rex Mulyadi (Indo-MathEdu Intellectuals Journal, 2024)
Artificial Intelligence (AI) helps improve efficiency, personalized learning, effective feedback, teaching effectiveness, as well as prepare students for a world increasingly dominated by technology. In today's digital era, the field of education has witnessed a significant transformation through the integration of Artificial Intelligence (AI). The purpose of this research is to determine the impact of AI in high school learning. The research approach that the compiler uses is a qualitative method with a type of literature study. Data is collected through various relevant article sources. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing. The result of this study is that the use of artificial intelligence (AI) has a significant impact on technological development in high school students and the education system, the application of new technology and new programs certainly has positive and negative impacts depending on how the user is. So it can be concluded that AI in high school learning if used properly and correctly will have a positive impact and avoid negative impacts